Establishment of KEL*01 and KEL*02 Genotyping to Recruit Uncommon, Kell-positive, Reagent Red Cells among Thai Blood Donors - Kamphon Intharanut (2020)
© 2019 Verlag Klinisches Labor GmbH. All rights reserved. Background: The reagent red blood cells used to screen and identify antibodies have to include K+ cells in all batch productions. The data of K/k phenotypes among differing Thai blood donor populations remains unknown; hence, mass screening for uncommon K+ donors by serological test has some limitations. Implementing K/k genotyping may be useful to predict uncommon K+ donors to overcome this challenge. This study aimed to establish an in-house K/k genotyping technique and to report KEL*01 and KEL*02 allele frequencies among three Thai blood donor populations to increase the selection of K+ donors in rare blood group databases. Methods: A total of 2,239 DNA samples obtained from 1,512 central, 427 southern, and 300 northern Thai blood donors were included. The KEL*01 and KEL*02 genotyping using PCR with sequence-specific primers (PCR-SSP) was developed and validated. All samples were genotyped using developed PCR-SSP. Moreover, the possibility of finding group O and predicted K+ phenotypes among Thai blood donor populations was calculated. Results: The DNA controls were validated using two sets of primer combinations and the results of KEL*01 and KEL*02 genotyping were in agreement. The KEL*01 allele frequencies were 0.0007, 0.0047, and 0.0000, and KEL*02 allele frequencies were 0.9993, 0.9953, and 1.0000 among central, southern, and northern Thai donors, respectively. In addition, mass screening among 3,795 and 566 donors in central and southern Thai populations was required to find at least one group O and predicted K+ phenotypes. Conclusions: The in-house PCR-SSP for KEL*01 and KEL*02 genotyping provided reproducible and accurate results with cost effectiveness. Our results confirmed the low KEL*01 allele frequencies among Thais. PCR-SSP could be used as an alternative technique to simply increase the number of uncommon predicted K+ phenotypes for reagent red blood cell recruitments.